2012
DOI: 10.1037/a0025938
|View full text |Cite|
|
Sign up to set email alerts
|

Interactions between serotonin transporter gene haplotypes and quality of mothers' parenting predict the development of children's noncompliance.

Abstract: The LPR and STin2 polymorphisms of the serotonin transporter gene (SLC6A4) were combined into haplotypes that, together with quality of maternal parenting, were used to predict initial levels and linear change in children’s (N = 138) noncompliance and aggression from age 18 –54 months. Quality of mothers’ parenting behavior was observed when children were 18 months old, and nonparental caregivers’ reports of noncompliance and aggression were collected annually from 18 to 54 months of age. Quality of early pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 83 publications
1
44
2
Order By: Relevance
“…Although in the current case, child SLC6A4 was unrelated to parenting (rendering evocative rGE unlikely), an unmeasured common genotype underlying noncompliance might increase the chance of negative parenting as well as the level of child noncompliance without any direct causal effect of parenting on child behavior. The same limitations are inherent in our own correlational studies of various parameters of differential susceptibility (e.g., BakermansKranenburg & Van IJzendoorn, 2006) and in the other studies reported in this issue (Eisenberg et al, 2012;Gibbons et al, 2012).…”
Section: Limitations Of Correlational Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Although in the current case, child SLC6A4 was unrelated to parenting (rendering evocative rGE unlikely), an unmeasured common genotype underlying noncompliance might increase the chance of negative parenting as well as the level of child noncompliance without any direct causal effect of parenting on child behavior. The same limitations are inherent in our own correlational studies of various parameters of differential susceptibility (e.g., BakermansKranenburg & Van IJzendoorn, 2006) and in the other studies reported in this issue (Eisenberg et al, 2012;Gibbons et al, 2012).…”
Section: Limitations Of Correlational Studiesmentioning
confidence: 87%
“…The study by Sulik et al (2012) is a case in point. They studied the interaction of genetic polymorphisms of the serotonin transporter (SLC6A4 or 5-HTTLPR) gene with quality of early maternal parenting in the prediction of noncompliance and aggression at 18 months and changes from 18 to 54 months.…”
Section: Limitations Of Correlational Studiesmentioning
confidence: 98%
“…However, racial and developmental differences regarding which allele functions as the susceptibility allele have also been suggested (Davies & Cicchetti, 2013; Sulik et al, 2012). As such analyses within specific developmental time periods, well-defined racial groups, and with carefully characterized environmental differences, are needed to disentangle these interactions (van IJzendoorn, et al, 2011).…”
Section: The 5httlpr S/s As a Susceptibility Genotypementioning
confidence: 99%
“…The second development is the increasing diversity of phenotypes that are being tested: these include quality of maternal parenting [26], affective state during marriage [27], risky sexual behavior [28], childhood emotionality [29], job satisfaction [30], perceived racial discrimination [31], adult unresolved attachment [32], and gaze bias [33]. A common feature of all these studies is the relatively small sample size: all except one [30] use samples of less than a thousand, and sometimes less than one hundred subjects [32].…”
Section: Candidate Gene Studies: Brain Imaging and G × Ementioning
confidence: 99%